On Fulfillment of Energy Conservation Law in Theory of Elastic Waves - V. V. Nevdakh (Наука и техника)
In accordance with the energy conservation law, the total energy of a closed physical system must remain constant at any moment of time. The energy of a traveling elastic wave consists of the kinetic energy in the oscillating particles of the medium and the potential energy of  its elastic deformation. In the existing theory of elastic waves, it is believed that the kinetic and potential energy densities of a traveling wave without losses  are the same at any moment of time and vary according to the same law. Accordingly, the total energy density of such wave is different at various moment of time, and only its time-averaged value remains constant. Thus, in the existing theory of elastic waves, the energy conservation law is not fulfilled. The purpose of this work is to give a physically correct description of these waves. A new description of a sound wave in an ideal gas has been proposed and it is based on the use of a wave equation system for perturbing the oscillation velocity of gas particles, which determines their kinetic energy, and for elastic deformation, which determines their potential energy. It has been shown that harmonic solutions describing the oscillations of the gas particles velocity perturbation and their elastic deformation, which are phase shifted by p/2, are considered as physically correct solutions of such equations system for a traveling sound wave. It has been found that the positions of the kinetic and potential energy maxima in the elastic wave, described by such solutions, alternate in space every quarter of the wavelength. It has been established that every quarter of a period in a wave without losses, the kinetic energy is completely converted to potential and vice versa, while at each spatial point of the wave its total energy density is the same at any time, which is consistent with the energy conservation law. The energy flux density of such traveling elastic wave is described by the expression for the Umov vector. It has been concluded that such traveling sound wave without losses  in an ideal gas can be considered as a harmonic oscillator.